Women's experiences of personalised support for asthma care during pregnancy: A systematic review of the literature. Issue 1 (December 2017) - Williamson, Graham; O'Connor, Anita; Kayleigh, Elmslie-Jones
Abstract Background Asthma and pregnancy are both sources of anxiety for women. Although there has been a focus on physiological management of asthma and pregnancy, there has been little research on the impact that personalised support can have on asthma care during pregnancy. This systematic review and narrative synthesis of the literature set out to answer the question 'What are women's experiences of asthma care, its management and education, during pregnancy?' Methods This systematic review was carried out using accepted methodology from the York Centre for Reviews and Dissemination. Electronic database searches were conducted using PsycInfo, CINAHL, MedLine, Google Scholar and the Cochrane Library, using the combination search terms: 'Asthma' AND 'Pregnancy' AND 'Care' AND ('Education OR Information OR Experience'). Hand searching of journals and searches for grey literature were also undertaken. Independent quality appraisal by the three authors took place using the criteria detailed by Kmet et al. (Standard Quality Assessment Criteria for Evaluating Primary Research Papers from a Variety of Fields, 2004). Results All papers scoring in excess of 60% were deemed to be of adequate quality for inclusion, of which there were five: two qualitative designs and three quantitative designs. The designs were too methodologically heterogeneous to permit statistical meta-analysis so narrative review and synthesis was undertaken. Despite an embryonic evidence bases, it is reasonable to conclude that personalised care has beneficial outcomes for pregnant asthmatic women. Conclusions Larger randomised controlled trials investigating personalised care are required to build an evidence base which can establish the efficacy of such interventions.